Rekonstruksi Filsafat Hukum di Tengah Krisis Normatif: Kajian Kualitatif Deskriptif atas Wacana Keadilan dan Moralitas dalam Hukum Kontemporer: Rekonstruksi Filsafat Hukum di Tengah Krisis Normatif: Kajian Kualitatif Deskriptif atas Wacana Keadilan dan Moralitas dalam Hukum Kontemporer - Sartono, Sartono; Rahmat, Sandy Marzuqi; Fariska, Nurshela; Jafar, Faozi; Arfiyah, Gemah; Prayuti, Yuyut; Sapsudin, Asep (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The development of law in the modern and post-modern era has brought significant epistemological consequences to the philosophical foundations that support it. In the midst of global disruption, the crisis of legitimacy of legal institutions, and the growing awareness of the importance of moral values and substantive justice, the philosophy of law is required to not only answer questions about “what the law is”, but also “why the law applies” and “how the law should be lived ethically”. This research aims to reconstruct the new direction of legal philosophy through a descriptive qualitative approach with a systematic literature review method. This study examines classic and contemporary works in legal philosophy, including the thoughts of Plato, Aristotle, Aquinas, Austin, Hart, Fuller, Dworkin, Habermas, to postmodern criticism in Critical Legal Studies and feminist legal theory. The findings show that the reduction of law to a mere normative system without an ethical-moral basis has created an acute normative crisis in contemporary legal praxis. This article proposes a transformative legal philosophy paradigm that not only emphasizes formal legality, but also integrates communicative rationality, public morality, and deliberative participation as the basis for the reconstruction of just and humane law. The implications of this approach provide a theoretical contribution to the development of a more holistic legal discourse, as well as presenting practical and managerial recommendations for policy makers in designing value-based regulations.